Decoded - Mai, Jia 1963- (Farrar, Straus and Giroux, 2015)
"One of China's bestselling novels, an unusual literary thriller that takes us deep into the world of code breaking In his gripping debut novel, Mai Jia reveals the mysterious world of Unit 701, a top-secret Chinese intelligence agency whose sole purpose is counterespionage and code breaking. Rong Jinzhen, an autistic math genius with a past shrouded in myth, is forced to abandon his academic pursuits when he is recruited into Unit 701. As China's greatest cryptographer, Rong discovers that the mastermind behind the maddeningly difficult Purple Code is his former teacher and best friend, who is now working for China's enemy--but this is only the first of many betrayals. Brilliantly combining the mystery and tension of a spy thriller with the psychological nuance of an intimate character study and the magical qualities of a Chinese fable, Decoded discovers in cryptography the key to the human heart. Both a riveting mystery and a metaphysical examination of the mind of an inspired genius, it is the first novel to be published in English by one of China's greatest and most popular contemporary writers."--Provided by publisher.